Clinical and electrographic features of persistent seizures and status epilepticus associated with anti‐NMDA receptor encephalitis (anti‐NMDARE). Issue 6 (21st January 2021) - Gofshteyn, Jacqueline S.; Yeshokumar, Anusha K.; Jette, Nathalie; Thakur, Kiran T.; Luche, Nicole; Yozawitz, Elissa; Varnado, Shelley; Klenofsky, Britany; Tuohy, Mary Claire; Ankam, Jyoti; Torres, Sarah; Hesdorffer, Dale; et al.
Abstract: Aims . Based on a multicenter cohort of people with anti‐NMDA receptor encephalitis (anti‐NMDARE), we describe seizure phenotypes, electroencephalographic (EEG) findings, and anti‐seizure treatment strategies. We also investigated whether specific electrographic features are associated with persistent seizures or status epilepticus after acute presentation. Methods . In this retrospective cohort study, we reviewed records of children and adults with anti‐NMDARE between 2010 and 2014 who were included in the Rare Epilepsy of New York City database, which included the text of physician notes from five academic medical centers. Clinical history ( e.g ., seizure semiology) and EEG features ( e.g ., background organization, slowing, epileptiform activity, seizures, sleep architecture, extreme delta brush) were abstracted. We compared clinical features associated with persistent seizures (ongoing seizures after one month from presentation) and status epilepticus, using bivariate and multivariable analyses. Results . Among the 38 individuals with definite anti‐NMDARE, 32 (84%) had seizures and 29 (76%) had seizures captured on EEG. Electrographic‐only seizures were identified in five (13%) individuals. Seizures started at a median of four days after initial symptoms (IQR: 3–6 days). Frontal lobe‐onset focal seizures were most common ( n =12; 32%). Most individuals (31/38; 82%) were refractory to anti‐seizure medications. Status epilepticus was associated with younger age (15 years [9–20] vs. 23 years [18–27]; p =0.04) and Hispanic ethnicity (30 [80%] vs. 8 [36%]; p =0.04). Persistent seizures (ongoing seizures after one month from presentation) were associated with younger age (nine years [3–14] vs. 22 years [15–28]; p <0.01). Measured electrographic features were not associated with persistent seizures. Conclusions . Seizures associated with anti‐NMDARE are primarily focal seizures originating in the frontal lobes. Younger patients may be at increased risk of epileptogenesis and status epilepticus. Continuous EEG monitoring helps identify subclinical seizures, but specific EEG findings may not predict the severity or persistence of seizures during hospitalization.